Genetic Diversity of Curculigo Latifolia Based on Morphological Characteristics and ISSR Markers - Ranjbarfard, Ali (2011)
Studies were conducted to establish a germplasm collection of Curculigo latifolia from Peninsular Malaysia, to describe the morphological characteristics of the collection, to analyze diversity and relationships within and among the populations based on morphological characteristics and to analyze molecular diversity and relationships within and among the populations using ISSR markers. Curculigo latifolia is a perennial shrub from the family Hypoxidaceae with great potential for the pharmaceutical industry. A germplasm collection consisted of 225 samples representing 45 populations from 11 states of Peninsular Malaysia was established. Curculigo latifolia was found growing under various environmental conditions including primary forests, undisturbed secondary forests, plantations (especially rubber plantations) and along roadsides, thus proving its high adaptability to a wide variety of ecological niches in Peninsular Malaysia. The genetic diversity of the germplasm collection was estimated using 28 qualitative and quantitative morphological characteristics and seven ISSR molecular markers. Results indicate that high morphological and molecular variations existed within and among the 45 populations of C. latifolia collected. Red leafstalk, hard leaf texture and hairy abaxial leaf surface were found to be identical in Populations 1, 2, 4, 13, 14, 15 and 40, while there were common qualitative characteristics among populations such as green leaf colour and glabrous adaxial leaf surface. Results of analysis of variance revealed that there were significant differences among the populations studied for all the quantitative characteristics measured. The 45 populations collected were grouped into several diverse clusters based on their morphological characteristics using UPGMA clustering method. The three dendrograms constructed based on qualitative morphological characteristics, quantitative morphological characteristics and a combination of both sets of data, revealed that Populations 1, 2, 4, 13, 14, 15 and 40 were distinctly detached from the other populations studied. ISSRs were found to be informative molecular markers for investigating genetic diversity among the C. latifolia populations as indicated by the high Nei’s gene diversity coefficient and Shannon’s information index (0.37 and 0.55, respectively). Results showed that AG and CA microsatellite repeats exhibited high polymorphism. The populations collected from Pahang were found to have the highest number of polymorphic bands among the populations studied. The relatively high coefficient ofgenetic differentiation (GST) obtained (0.48) revealed that C. latifolia is a cross-pollinating species. Populations 1, 2, 13, 14, 15 and 40 were found to be distinctly separated from all other populations studied. The results were similar to those revealed by the cluster and PCA analyses based on morphological characteristics. Although similarity coefficients among the populations studied obtained from morphological characteristics and molecular markers were found not to be correlated with each other, both morphological and molecular characterizations revealed that Populations 1, 2, 13, 14, 15 and 40 were distinctly different from the other populations. This indicates major differences in morphology and genome composition between these populations and the other populations studied.